2013
DOI: 10.1155/2013/852754
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Caloric Restriction and Exercise Improve Metabolic Conditions of Dietary-Induced Obese Mice in Autophagy Correlated Manner without Involving AMPK

Abstract: Aim. To investigate the role of AMPK activation and autophagy in mediating the beneficial effects of exercise and caloric restriction in obesity. Methods. Dietary-induced obesity mice were made and divided into 5 groups; one additional group of normal mice serves as control. Mice in each group received different combinations of interventions including low fat diet, caloric restriction, and exercise. Then their metabolic conditions were assessed by measuring serum glucose and insulin, serum lipids, and liver fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 17 publications
5
44
1
1
Order By: Relevance
“…Interestingly, there were no differences in LC3 expression observed between DR and AL mice, suggesting that macro-autophagy was not modulated by HFDR in our study. This is in contrast to other studies, where induction of LC3-related autophagy was found in muscle after HFDR 31 and in liver after lowfat DR. In contrast to Hsp70 and Hsc70, other heat shock proteins, namely ER chaperones, have been found to be transcriptionally down-regulated in the liver under calorie restriction conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there were no differences in LC3 expression observed between DR and AL mice, suggesting that macro-autophagy was not modulated by HFDR in our study. This is in contrast to other studies, where induction of LC3-related autophagy was found in muscle after HFDR 31 and in liver after lowfat DR. In contrast to Hsp70 and Hsc70, other heat shock proteins, namely ER chaperones, have been found to be transcriptionally down-regulated in the liver under calorie restriction conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports have already suggested that 6-10 weeks of DR on a high-fat diet can improve metabolic health parameters including reduction of plasma insulin, glucose, and leptin levels similar to low-fat diets, [31][32][33] although HFDR for shorter periods (3 weeks) may be rather marginally effective. 34 In contrast to other HFDR studies that focused on white adipose tissue 33,35 and arterial function, 9 we investigated potential longevity-related and nutrient-sensing pathways in the liver on 6 months of HFDR.…”
Section: Discussionmentioning
confidence: 95%
“…flux was greater in glycolytic versus highly oxidative muscle, and this was related to AMPK and mammalian target of rapamycin activities, which are both important determinants of autophagy (11,13,30,31). The regulatory events required to induce autophagy were attenuated with aging in skeletal muscle (15).…”
Section: Discussionmentioning
confidence: 99%
“…Another mouse model of stimulus-deficient autophagy, the BCL2 AAA mice, which contain knock-in mutations in BCL2 phosphorylation sites (Thr69Ala, Ser70Ala, and Ser84Ala) that prevent autophagy activation, showed altered glucose metabolism during acute exercise and impaired chronic exercise-mediated protection against HFD-induced glucose intolerance (10). Others have reported activation of autophagy in skeletal muscle in response to exercise and caloric restriction (11)(12)(13)(14). The ability to induce autophagy has been shown to deteriorate with aging in skeletal muscle (15).…”
mentioning
confidence: 99%
“…Since our first report of increased cardiac autophagy in the type 2 diabetic fructose-fed mouse (59), the experimental literature in this field has expanded considerably, but it is not yet possible to synthesize a comprehensive understanding. Relying on a variable selection of molecular tools, states of increased (4,12,49,50,59,61,78,93,102), unchanged (47,48,57,62), and decreased (6,23,28,29,73,82,101,103,104,110) basal cardiac autophagy activity have all been reported in diabetic/ insulin resistant contexts (see Table 1). These discrepancies are not necessarily attributable to the different models of diabetes, since contrasting findings have been observed within the same diabetic model [e.g., STZ-mouse: increased LC3BII (12) vs. decreased LC3BII (103)].…”
Section: )mentioning
confidence: 99%